2000
DOI: 10.1021/tx000050h
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of the Antagonism between Inorganic Mercury and Selenium in Mammals

Abstract: Mercuric chloride toxicity in mammals can be overcome by co-administration of sodium selenite. We report a study of the mutual detoxification product in rabbit plasma, and of a Hg-Se-S-containing species synthesized by addition of equimolar mercuric chloride and sodium selenite to aqueous, buffered glutathione. Chromatographic purification of this Hg-Se-S species and subsequent structural analysis by Se and Hg extended X-ray absorption fine structure (EXAFS) spectroscopy revealed the presence of four-coordinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
124
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(135 citation statements)
references
References 35 publications
6
124
0
5
Order By: Relevance
“…Many studies have been carried out to examine the role of selenium in the detoxification of mercury 20) . Although the complete mechanism of mercury-selenium interaction is still unresolved, there is evidence that selenium in plasma forms a complex with mercury, which then binds to selenoprotein P 21,24) . Formation of mercury-selenium complex with selenoprotein P causes redistribution of mercury in the organism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have been carried out to examine the role of selenium in the detoxification of mercury 20) . Although the complete mechanism of mercury-selenium interaction is still unresolved, there is evidence that selenium in plasma forms a complex with mercury, which then binds to selenoprotein P 21,24) . Formation of mercury-selenium complex with selenoprotein P causes redistribution of mercury in the organism.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the ability of selenium to reduce mercury toxicity has been extensively investigated 20,21) . Most studies have evaluated the effects of the inorganic selenium compound (sodium selenite) on mercury toxicity 9,11,[22][23][24][25] . In the presence of selenium, the accumulation of mercury in the target organ kidney is reported to be reduced, but body retention of mercury on the whole is increased, especially in the liver 20) .…”
Section: Introductionmentioning
confidence: 99%
“…Such mixtures can cause unexpected effects leading to potential interactions among toxicants that result in additive, antagonistic, or potentiation effects. Selenium (Se) and mercury (Hg) were chosen for study in part because of the well documented antagonistic relationships between Se and Hg in fish (Ganther et al 1972), birds (Welsh and Soares 1976), and mammals (Gailer et al 2000). An additive relationship occurs when the toxicity of the mixture can be predicted from the dose-response curve for each component, assuming that each component acts independently and has a different mode of toxic action (Bliss 1939).…”
mentioning
confidence: 99%
“…The alleviation of inorganic Hg toxicity by Se was reported as early as 1967, and the chemical mechanism of antagonism between sodium selenite and mercuric chloride has been described in mammalian tissue (Gailer et al 2000). The mechanism consists of selenite being taken up by erythrocytes and reduced and expelled as selenide, which then reacts with albumin-bound mercuric Hg to form an Hg-Se-S species that binds to selenoprotein P. The first report of the interaction between organic Hg (MeHg) and Se was by Ganther et al (1972), and it clearly showed the alleviating affects of sodium selenite on MeHginduced toxicity in rats, although the mechanism is not known.…”
mentioning
confidence: 99%
“…They also describe and discuss the relationships between mercury and selenium species in the tissues. Further studies are required to improve our understanding of the interactions between mercury and selenium described by Gailer et al (2000).…”
Section: Mining and Pollution: Effects On Biotamentioning
confidence: 99%